(untitled) (Research, Society and Development, 2021)
This work aims to determine the relationship between working capital and business efficiency levels. It is important to highlight the favorable effects of civil construction works on the economic and social growth and development of a region, but it is also necessary to stop and analyze whether their execution is accompanied by efficiency and productivity criteria that affect cost reduction, for example. It is necessary to analyze the way this process is managed, especially if technical and managerial deficiencies were identified that hinder the achievement of objectives related to meeting deadlines, costs and, in some cases, quality in the execution of public works. In view of this, it was identified that the lack of adequate planning and the low quality of professionals responsible for the design and execution of works would be the main causes, among others, of these deficiencies. In these circumstances, it is mandatory that companies improve their capabilities for the conception, design and execution of works in a way that contributes to the well-being and satisfaction of their customers’ needs.